SCHOOL OF INDUSTRIAL ENGINEERING IN SAN MARCOS - Quispe Atúncar, Carlos A. (1998)
In 1957 the National University of San Marcos, in order to investigate the most pressing human problems posed by the economic and social reality of the country, created the Institute of Human Relations and Productivity, to train experts in Personnel Management, Analysis Cost and Market and Labor Relations. In 1960 the Institute became the Graduate School of the Faculty of Economic Sciences, to train experts in Public Relations and Advertising, Industrial Relations and Production Engineering and Management. This training was aimed at those who had completed college and leading to diplomas of Experts.